Пасхальный обход дворов у старообрядцев белорусско-литовского пограничья - Александрович Новиков, Юрий (Slavistica Vilnensis, 2002)
This Old Believer ritual, which is widespread under the name voločebnyj (voločobnyj) in Belarus, adjacent regions of Lithuania, and western Russia, is reported here for the first time. Data collected during expeditions in 2000–2002 shows that Old Believers in several parishes on the Byelorusian-Lithuanian border practiced this ritual until just recently. It is proposed that the ritual was not borrowed from neighboring peoples, but was brought by the Old Believers from their former homeland.